On the numerical simulation of laser beam cutting of hollow sphere structures - Araújo, Manuel António (2013)
Laser beam cutting is a highly efficient technique to cut materials. The relatively small amount of energy being involved during the process results in a small heat affected zone. This characteristic makes laser beam cutting interesting for composite materials. Within this paper the cutting process is applied to metallic hollow sphere structures (MHSS), a relatively new group of advanced composite materials. The metallic hollow sphere structures combine the well-known advantages of cellular metals without major scattering of their material parameters. They are characterised by high geometry reproduction leading to relatively constant mechanical and physical properties. Numerical simulation is used in order to define proper process parameters for a large variety of metallic hollow sphere structures. The finite element method based simulation covers material parameters as well as process parameters like the cutting velocity. Heat conduction, convection and heat radiation is taken into account. The temperature distribution is our fundamental result. It should be mentioned that phase change from solid to liquid state is also included in the computational procedure.